1990
DOI: 10.1182/blood.v76.7.1438.1438
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of transfusion-related acute lung injury in an ex vivo lung model [see comments]

Abstract: Leukoagglutinins are implicated in transfusion-related acute lung injury (TRALI). In the present study, severe lung vascular leakage was reproduced by application of a leukoagglutinating antibody of anti-5b specificity in an ex vivo lung model. The antibody originated from a multiparous donor-plasma, observed to cause noncardiogenic edema during transfusion therapy. Heated full plasma (anti-5b-titer 1/128) or purified immunoglobulin G fraction was used for the studies. Ex vivo isolated rabbit lungs were perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(107 citation statements)
references
References 31 publications
1
104
0
2
Order By: Relevance
“…During the second infusion, the antibody could provoke further activation of the primed monocytes and release of soluble mediators, for example cytokines, which would then activate and recruit granulocytes. Subsequently, the granulocytes could become trapped in the vascular endothelium of the lung, causing damage to endothelial cells with the subsequent influx of fluid into the interstitium (as suggested by Seeger et al, 1990). The abnormally high granulocyte concentration at the time of monocyte recovery, together with the increase in body temperature, indicates immunological activation processes.…”
Section: Discussionmentioning
confidence: 99%
“…During the second infusion, the antibody could provoke further activation of the primed monocytes and release of soluble mediators, for example cytokines, which would then activate and recruit granulocytes. Subsequently, the granulocytes could become trapped in the vascular endothelium of the lung, causing damage to endothelial cells with the subsequent influx of fluid into the interstitium (as suggested by Seeger et al, 1990). The abnormally high granulocyte concentration at the time of monocyte recovery, together with the increase in body temperature, indicates immunological activation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture and animal studies using models of TRALI have detected the release of inflammatory mediators and cytokines by neutrophils, which are incriminated in the pathogenesis of the syndrome (Grimminger et al, 1991;Wyman et al, 2002). Activation of neutrophils by anti-HLA antibodies induces endothelial adhesion molecule expression and cell death in cultured EC (Nishimura et al, 2007;Silliman et al, 2007), and permeability increases in perfused intact microvessels (Seeger et al, 1990); the mechanism of neutrophil activation however is not well understood. Since many patients receiving transfusions with antibodies to their white blood cells do not develop TRALI, it has been postulated that prior neutrophil activation and adhesion to lung EC in the setting of sepsis or other inflammatory condition is necessary for TRALI development (Silliman, 2006).…”
Section: Transfusion-related Acute Lung Injurymentioning
confidence: 99%
“…Furthermore, in a study by Sachs et al using an ex vivo rat model of anti-CD177-mediated TRALI, complement was not found to be required for TRALI induction (TRALI induction was more dependent on the density of the cognate antigen), as TRALI occurred in a complement-free environment [48]. In an earlier ex vivo TRALI study by Seeger and colleagues using rabbit lungs, rabbit plasma was suggested to have served as a source of complement and induced TRALI together with anti-5b (anti-HNA-3a) antibodies and PMNs [49]. In this study, however, there was no direct investigation regarding the contribution of complement.…”
Section: Evidence For the Involvement Of Complement In Tralimentioning
confidence: 99%